Analisis Terapi Komplementer Yoga Terhadap Penyalahgunaan Napza Pada Remaja - Indirawaty, Indirawaty; Syarif, Kurnia Rahma; Genggeng, Rosita; Sumirah, Sumirah (Magister Pendidikan Nonformal Pascasarjana Universitas Negeri Gorontalo, 2020)
According to Riskesdes data (2018), the prevalence of mental disorders has increased when compared to the 2013 Riskesdes from 1.7% to 7%. In addition, the prevalence of mental emotional disorders in people aged> 15 years rose from 6% to 9.8%. Based on the results of data analysis the World Drug Report states that in this decade showed about 208 million people or 5% of the world's population who use narcotics and other addictive substances. Users of narcotics, psychotropic substances and other addictive substances are aged 15 years to 64 years and it is estimated that in 2025 it will increase to 15% of the world's population (Syahrial, 2015). One method that can be used to help control depression or mood due to narcotics consumption is complementary yoga therapy (Streeter, Gerbarg, Domenic, & Brown, 2012). The research design used was quasy experimental. In this study, One group pretest posttest design. The subjects in this study were 40 people with kiteria. The results of the study are based on paired t test results obtained that the value of the statistical test results obtained p value (0,000) <0.05 which means there is a difference in knowledge scores between before and after the intervention while the statistical test results obtained p value (0,000) <0.05 which means there is a difference in scores attitude between before and after the intervention. So it can be concluded that complementary yoga therapy can increase knowledge and attitudes on drug abuse.